Tuberculosis as Public Health Problem in the Slovak Republic - Samohyl, Martin; Solovic, Ivan; Svecova, Jana; Rams, Roman; Hirosova, Katarina; Jurkovicova, Jana (Iranian journal of public health, 2017)
Tuberculosis as Public Health Problem in the Slovak Republic